KARAKTER/SIFAT FISIK KIMIA KEJU RENDAH LEMAK DARI BERBAGAI BAHAN BAKU SUSU MODIFIKASI - Juniawati Juniawati; Sri Usmiati; Evy Damayanthi (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2015)
Low-fat cheese is a dairy product that is potentially developed to meet the public demand for healthy food. Milk modification is oneof the low-fat cheese processing technology to improve the physical characteristics of low-fat cheese. This research aimed to studythe effect of modification of milk to physico chemical characteristic of low-fat cheese. Milk modification as a treatment is consistingof five (5) formulae : reduction of 60% milk fat (A1), corn oil emulsion in the skim milk (A2), corn oil emulsion with a dispersionof whey protein concentrate (WPC) in skim milk (A3), emulsion W1 / O / W2 in skim milk (A4), corn oil emulsion in the skim milkplus probiotics (A5). Each cheese-making process for each treatment carried out in the scale of 20 liters of milk. This study used arandomized block design with two replication. Data were analyzed using analysis of variance, with the mean difference of Duncantest. Low-fat cheese in this study resulted from the formula A3 is a mixture of corn oil emulsion with a dispersion of whey proteinconcentrate in skim milk (fat content of 24.59% bk). Low-fat cheese A3 has a 7.71% yield, hardness 171.45gf, moisture 48.98%,protein 27.35%, fat 12.25%, calcium 328.91 mg /100g, phosphorus 16.31 mg /100g, and NaCl 1.21%.